Sistem Pengolahan Persediaan Ayam Boiler Berbasis Web Mobile - Krisna, Anan; Alita, Debby; Samsugi, S. (Jurnal Media Borneo, 2024)
Berkah Unggas Farm Jati Agung is a form of individual business engaged in the business of buying and selling boiler chickens. Based on interviews with the owner of Berkah Unggas Farm that the process of processing chicken inventory data is processing and recording that still uses manual methods (recording using a ledger) so that data inaccuracies, there is a high risk of human error, such as data writing errors, such as incorrect stock or errors in recording transactions. Data inaccuracies can lead to incorrect decisions and disrupt the operational efficiency of boiler chicken entry and exit. Based on these problems, a mobile web-based boiler chicken management system was created. The system, designed and built using the waterfall system development method, and the system was tested using ISO 25010. The system that has been built can help the process of processing chicken inventory data that produces more accurate data, minimizing the risk of human error, especially in data processing, such as data writing errors, such as incorrect stock or errors in recording transactions, facilitating boiler chicken inventory management faster than the previous system. The results of system feasibility testing using ISO 25010 get results of 97%. On a likert scale that the feasibility of the information system that has been made has a very good success, so that the system is feasible to be implemented and implemented at Berkah Unggas Farm Jati Agung.